Application of ionic liquids in the leaching and extraction of precious metal from electronic waste - Masilela, Mthobisi Delisa (My University, 2018)
Electronic waste (e-waste) contains valuable materials such as metals, which may be recovered using different processes such as conventional pyrometallurgy or hydrometallurgy. Existing metal recovery methods have a number of limitations which include adverse environmental footprints, therefore necessitating the investigation into other methods or reagents. In this research, ionic liquids were investigated for both leaching of gold (Au) and silver (Ag) from e-waste material and their extraction from leach solutions. The ionic liquid [Bmim][HSO4] together with thiourea as a lixiviant and Fe2(SO4)3 as an oxidant was investigated for the leaching of Ag and Au from pulverized printed circuit board sample containing 162 g/t Au and 618 g/t Ag. On the other hand, [Bmim][Tf2N], [Bmim][PF6], and Cyphos 101 were investigated as extractants for Ag and Au from chloride and glycine-histidine leach liquors of the printed circuit board samples. Ag and Au dissolution in the ionic liquid [Bmim][HSO4] leaching system was observed. However, the leaching efficiencies recorded were low with Au efficiency at 24% in a leaching solution of 30% [Bmim][HSO4] and the efficiency of Ag only at 3% in the same solution. The ionic liquids [Bmim][Tf2N], [Bmim][PF6], and Cyphos 101 were efficient for gold extraction from aqua regia leach liquor with more than 90% of Au extracted. Ag extraction was lower compared to Au, with no extraction recorded for [Bmim][Tf2N] but over 90% extraction was recorded for both Cyphos 101 and [Bmim][PF6]. The ionic liquids did not extract any of the two metals from the alkaline glycine-histidine leach liquors.
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Environmental Sciences, Johannesburg 2018
Keywords: Electronic waste; Electronic apparatus and appliances